TM3-4 The effect of acetazolamide on intracranial pressure: primary study with prolonged continuous intracranial pressure monitoring. Issue 3 (14th February 2019) - Thompson, S; Chan, H; Thorne, L; Watkins, L; Toma, A
Abstract : Objectives: Acetazolamide has frequently been used as a first-line treatment for idiopathic Intracranial Hypertension (IIH) and other disorders which lead to a non-acute rise in intracranial pressure (ICP). The effect of acetazolamide has been observed through lumbar puncture, however the effect of acetazolamide on ICP has not been studied in continuous ICP measurement. Design: A retrospective study of a prospectively built ICP database Subjects: All patients with continuous ICP monitoring demonstrating 24 hours on and 24 hours off acetazolamide were included in the study. Methods: Patients median ICP and median pulse amplitude over 24 hour monitoring period on and off Diamox was assessed. Results: 12 patients (9F, 3M) underwent ICP monitoring with data collected during the same admission. 8 patients had IIH, 1 Chiari Malformation, 3 new diagnostic ICP procedures. 10 patients saw a reduction in ICP while on acetazolamide. Overall, patients experienced a Median reduction of 1.14 mmHg (Mean 1.16 mmHg, Range 4.24 to −4.445 mmHg). Patients (n9) who were on ≥1 g of acetazolamide per day experienced a median reduction in ICP of 1.595 mmHg (Mean 1.91 mmHg, Range 4.24–0.5 mmHg). Conclusions: Our data suggests acetazolamide can reduce ICP quickly following commencement, however this reduction was relatively small. The effect seems greater with a higher dose. Larger numbers of patients are required to gain a greater understanding into the significance of acetazolamide on ICP, particularly the affect at larger doses.